Principles and Available Hardware in DECT - Alavandar, Ezhilmathi; Arunachalam, Venkatesh Kasi; Narappulan, Niyas; Mahadevan, Gowtham S.; Kashyap, Ravindar; Mehta, Pankaj; Cherian, Mathew (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Computed tomography (CT) has undergone a phenomenal evolution since its introduction in 1971 and has revolutionized diagnostic radiology. It is now the cornerstone of diagnostic imaging and has become an inevitable part of the management of patients. Among all the advancements and breakthroughs witnessed over the years, the most recent and most advanced is the dual-energy CT (DECT), also known as spectral CT, introduced in 2006. In DECT, two datasets are obtained by scanning with two different energy spectra (low and high energy). The difference in attenuation can differentiate materials with different elemental compositions but similar attenuation in single-energy CT. Therefore, it has widespread clinical applications based on its potential for material decomposition and virtual monoenergetic imaging. In this review, the principle and hardware of DECT will be presented with an overview of its clinical applications.
Keywords: CT; diagnostic imaging; DECT; attenuation; applications; principle